Đặc điểm các nguồn nước và vai trò của chúng đối với môi trường sinh thái vùng cát ven biển nam Quảng Bình - Trường, Phan Văn (Vietnam Journal of Earth Sciences, 2007)
The waters characteristic and the role of its with the ecological environment on coastal sand zone of the South Quang Binh